2012
DOI: 10.1093/glycob/cws132
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of free deaminoneuraminic acid (KDN)-containing complex-type N-glycans in human prostate cancers

Abstract: We previously reported on the accumulation of a substantial amount of free N-acetylneuraminic acid (Neu5Ac)-containing complex-type N-glycans in human pancreatic cancer cells (Yabu M, Korekane H, Takahashi H, Ohigashi H, Ishikawa O, Miyamoto Y. 2013. Accumulation of free Neu5Ac-containing complex-type N-glycans in human pancreatic cancers. Glycoconj J, 30(3):247-256). In the present paper, we further extend our cancer glycomic study of human prostate cancer. Specifically, we demonstrate that, in addition to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The increase and metabolic incorporation of Neu5Gc are associated with inflammation within a mechanism of interaction with circulating anti-Neu5Gc antibodies [34][35][36][37] . Not only Neu5Ac and Neu5Gc increase in expression in malignant tissues, but KDN-containing N-glycan also accumulates in significant amounts in prostate cancer tissues 9 . Altogether the alteration of Sia expression and the distribution might be involved with the pathogenesis of cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The increase and metabolic incorporation of Neu5Gc are associated with inflammation within a mechanism of interaction with circulating anti-Neu5Gc antibodies [34][35][36][37] . Not only Neu5Ac and Neu5Gc increase in expression in malignant tissues, but KDN-containing N-glycan also accumulates in significant amounts in prostate cancer tissues 9 . Altogether the alteration of Sia expression and the distribution might be involved with the pathogenesis of cancer.…”
Section: Discussionmentioning
confidence: 98%
“…They also investigated the accumulation of the same type of Sia in prostate cancers. Moreover, not only was the increase of free Neu5Ac-containing N-glycans found, but also significant amounts of free KDN-containing N-glycans accumulated in prostate cancer tissues 9 . It was the first study that showed unequivocal chemical evidence for the occurrence of KDN glycoconjugates in human tissues.…”
Section: Introductionmentioning
confidence: 99%
“…However, the levels of free N -glycans in normal colorectal and pancreatic tissues were barely detectable (Yabu et al 2013b ). In addition to the free Neu5Ac-containing N -glycans accumulated in pancreatic cancers, a relatively large amount of free KDN (deaminoneuraminic acid)-containing N-glycans were also found to accumulate in prostate cancer tissues from four out of fi ve patients (Table 12.2 ) (Yabu et al 2013a ). Indeed, in one of the four cases having bone metastasis, the free KDN-glycans are major components, and the amounts of the free KDN-glycans were much higher than those of GSLs in both primary and bone metastatic prostate cancer tissues.…”
Section: Free Oligosaccharidesmentioning
confidence: 99%
“…[4][5][6][7] Numerous reports of concerning HPLC analyses of pyridylamino (PA)-oligosaccharides have been published, and it is easy to compare the obtained HPLC data, and thus enabling the oligosaccharide structure to be deduced by two-or three-dimensional (2D/3D) HPLC mapping techniques that combine ion-exchange, normal, and reversedphase HPLC. [8][9][10][11] Furthermore, fragment ions of the PAoligosaccharides in MS/MS spectra can be easily characterized because there are differences in the mass number between a reducing-PA tagged end and a non-reducing free end; some databases that can automatically deduce the oligosaccharide structure from the fragmentation pattern in MS/MS spectra have been established. [12][13][14] However, an excess of 2-aminopyridine (2-AP) of more than a few thousand-fold is required in the reaction tube to reduce nonlabeled oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%